THE ROLES OF CODE SWITCHING IN ENGLISH AS A FOREIGN LANGUAGE: SPEAKING CLASS - Mohamad Ijudin; Leni Irianti; Etika Rachmawati (JALL (Journal of Applied Linguistics and Literacy), 2021)
This study highlights on the use of code switching in speaking class and its impact toward the students’ language development in target language. Code switching is a regular phenomenon in multilingual conversations. The purposes of the study are to discover the use and the roles of code switching in EFL classrooms, how the roles contributed to the students’ language development in the EFL context, and how the code switching influences the process of teaching in EFL classroom. The study gathered the data based on a qualitative research design. There were two instruments used in this study; classroom observations and questionnaire. The study was a case study in the teaching and learning process of Speaking for classroom instruction at the fourth semester students of English department in Galuh University, Ciamis. The findings of the study exposed that using code switching while teaching and learning process is valuable in the Speaking English as foreign language, in this case in the subject of Speaking for classroom instruction. The code switching as one of the kinds of multilingualism is essential and unavoidable in language classrooms.